Effects of Interseeding Ladino Clover into Tall Fescue Pastures of Varying Endophyte Status on Grazing Performance of Stocker Steers - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2017)
Sixty-four yearling steers grazing tall fescue pastures were used to evaluate the effects of fescue cultivar and interseeding ladino clover on grazing gains and available forage. Fescue cultivars evaluated were high-endophyte ‘Kentucky 31,’ low-endophyte ‘Kentucky 31,’ ‘HM4,’ and ‘MaxQ.’ Steers that grazed pastures of low-endophyte ‘Kentucky 31,’ ‘HM4,’ or ‘MaxQ’ gained significantly more (P<0.05) and produced more (P<0.05) gain/a than those that grazed high-endophyte ‘Kentucky 31’ pastures. Gains of cattle that grazed low-endophyte ‘Kentucky 31,’ ‘HM4,’ or ‘MaxQ’ were similar (P>0.05). High-endophyte ‘Kentucky 31’ pastures had more (P<0.05) available forage than lowendophyte ‘Kentucky 31,’ ‘HM4,’ or ‘MaxQ’ pastures.
Keywords: interseeding; ladino clover; tall fescue; grazing; stocker cattle; endophyte